ANALISIS DESKRIPTIF SISTEM PAYMENT PAJAK KENDARAAN BERMOTOR PADA APLIKASI SAMSAT MOBILE JAWA BARAT (SAMBARA) - Abyan Mu’aafii Satriya; Ayu Nugraheni (Journal of Management and Social Sciences, 2023)
the purpose of this study is to identify public service innovations, namely the SAMBARA (West Java Mobile Samsat) application in paying motor vehicle taxes. This research seeks to explore the benefits of this Sambara innovation for the people of West Java. This study used a qualitative research method with a literature study approach. Some of the findings from this research are that the Sambara innovation can make payments online, can find out a map of the Samsat location, can check vehicle data, can verify vehicle tax using the NIK and vehicle frame number. Other findings are supporting factors, namely cooperation and support from various parties as well as the position of the private sector which contributes to operational provision. However, in making tax payments the Sambara application still has problems and there is still low understanding and lack of information to the public about the Sambara application.